Validation of cause of death classification after heart transplantation and cause‐specific life expectancy compared to the general population. Issue 9 (28th June 2022) - Gjesdal, Grunde; Lundgren, Jakob; Czuba, Tomasz; Wareham, Neval Ete; Gustafsson, Finn; Nilsson, Johan; Smith, J. Gustav; Braun, Oscar Ö.
Abstract: Background: Post heart‐transplant survival has increased, but information is lacking on specific causes of death and life expectancy. We aimed to assess cause‐specific loss of life‐years compared to the general population, evaluate classification for cause of death after heart transplantation, and assess validity of cause of death data from the International Society of Heart and Lung Transplant (ISHLT) registry. Methods: In this single center study, we included 239 heart recipients transplanted between 1988 and 2019 in Lund, Sweden ( n  = 239, 50% of the transplanted population where the cause of death was available). Two cardiologists retrospectively assigned causes of death according to a published classification (CLASS) in the 91 recipients who died during follow‐up. Life expectancy was compared to data from the general population. Results: Compared to the average Swedish population, life expectancy for heart transplant recipients was 20 years shorter (IQR 12.9–27.2). The largest number of life‐years lost were for deaths due to acute (49 years) and chronic rejection (27 years). Primary graft dysfunction (24 years) accounted for 24% of deaths, followed by malignancy (20 years) and infection (17 years), each accounting for ∼20% of deaths. Use of CLASS revealed moderate inter‐rater agreement (56%) and moderate agreement with the ISHLT registry (62%). Conclusions: Survival after heart transplantation was 20 years lower than in the general population. In the young, more life‐years were lost due to acute graft rejection, whereas chronic graft rejection and primary graft failure were more important causes of death in older patients. Agreement was moderate between CLASS and the ISHLT registry classifications.